Computational Intelligence and Sustainable Systems Intelligence and Sustainable Computing - Anandakumar, H.; Arulmurugan, R.; Onn, Chow Chee (EAI/Springer Innovations in Communication and Computing,, 2019)
This book features research related to computational intelligence and energy and thermal aware management of computing resources. The authors publish original and timely research in current areas of power, energy, temperature, and environmental engineering as and advances in computational intelligence that are benefiting the fields. Topics include signal processing architectures, algorithms, and applications; biomedical informatics and computation; artificial intelligence and machine learning; green technologies in information; and more. The book includes contributions from a wide range of researchers, academicians, and industry professionals. The book is made up both of extended papers presented at the International Conference on Intelligent Computing and Sustainable System (ICICSS 2018), September 20-21, 2018, and other accepted papers on R&D and original research work related to the practice and theory of technologies to enable and support Intelligent Computing applications. Presents the most recent challenges and developments in computational intelligence for sustainable systems and their best practices for application; Includes high quality research contributions from a wide range of scholars, researchers, academicians and professionals; Features expanded papers from the International Conference on Intelligent Computing and Sustainable System (ICICSS 2018), September 20-21, 2018.